Pelatihan Membuat Es Buah di Lingkungan VIII Kelurahan Babura Kecamatan Medan Baru - Sianturi, Jeudi Agustina Taman Parulian; Sembiring, Rasmulia; Saragih, Henri; Sinurat, Elperida J.; Panjaitan, Maludin; Purba, Jon Henri; Butarbutar, Hotlan; Napitupulu, Junika; Nadapdap, Kristanty M. N.; Panjaitan, Mangasa (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
The aim of implementing community service is to train and direct the community to carry out various efforts to increase and increase household income. Various entrepreneurial innovations are efforts to increase people's income and can be done using various approaches. Carrying out training for women in Ward VIII, Babura Village - Medan Baru District. The PKM team conducted training in making fruit ice and are expected to be able to do it themselves to increase their income and for their own consumption. The participants paid serious attention to the training and were motivated to do so.